IDENTITAS BUDAYA NASIONAL PADA GAME NUSANTARA ONLINE - Harli Brata Wardhana; Didik Hariyanto (Kanal: Jurnal Ilmu Komunikasi, 2012)
Game Nusantara Online is the only online game that lifted the Indonesian culture hey day empires that ever existed and is the only original online games domestically-made. So it is not surprising that this game displays various types of display depicting national cultural identity in the game. The method used in analyzing was John Fiske the semiotics (semiology) through three tiers level, reality, representation, and ideology in the opening game in the form of nondialogue short film, but it was also analyzed in the game play in game logo, the cast of characters, and missions “Timun Mas”. Further analysis was based on the study of literature and other supporting data to determinenational cultural identity. After doing research on the game Nusantara Online, it was found that national cultural identity displayed on the level of reality by visualizing typical clothing and accessories of Indonesia empire at that time, the use of the name on the cast of characters that has its own story and has become the local culture, including Hayam Wuruk, Elephant Mada, and others. Visualization of social life, such as religious rituals Bendrong Dimples and Bali, and incorporate folklore or legends in the game missions. While the level of representation, the camera technique is used so that the details of the national cultural identity clearly visible on the clothing motif and shape of the building. The ideology that displayed the Nusantara Online games are games that have cultural values and history of Nusantara (Indonesia).